Risk factors of different mortality periods in older patients with end-stage renal disease undergoing urgent-start peritoneal dialysis: a retrospective observational study - Shizheng Guo; Liming Yang; Xueyan Zhu; Xiaoxuan Zhang; Zhanshan Sun; Lingfei Meng; Yangwei Wang; Jian Li; Siyu Cheng; Xiaohua Zhuang; Wenpeng Cui (BMC Geriatrics, 2024)
Abstract Background The first six months of therapy represents a high-risk period for peritoneal dialysis (PD) failure. The risk of death in the first six months is higher for older patients treated with urgent-start PD (USPD). However, there are still gaps in research on mortality and risk factors for death in this particular group of patients. We aimed to investigate mortality rates and risk factors for death in older patients with end-stage renal disease (ESRD) receiving USPD within and after six months of therapy. Methods We retrospectively studied the clinical information of older adults aged ≥ 65 years with ESRD who received USPD between 2013 and 2019 in five Chinese hospitals. Patients were followed up to June 30, 2020. The mortality and risk factors for death in the first six months of USPD treatment and beyond were analyzed. Results Of the 379 elderly patients in the study, 130 died over the study period. During the follow-up period, the highest number (45, 34.6%) of deaths occurred within the first six months. Cardiovascular disease was the most common cause of death. The baseline New York Heart Association (NYHA) class III–IV cardiac function [hazard ratio (HR) = 2.457, 95% confidence interval (CI): 1.200–5.030, p = 0.014] and higher white blood cell (WBC) count (HR = 1.082, 95% CI: 1.021–1.147, p = 0.008) increased the mortality risk within six months of USPD. The baseline NYHA class III–IV cardiac function (HR = 1.945, 95% CI: 1.149–3.294, p = 0.013), lower WBC count (HR = 0.917, 95% CI: 0.845–0.996, p = 0.040), lower potassium levels (HR = 0.584, 95% CI: 0.429–0.796, p = 0.001), and higher calcium levels (HR = 2.160, 95% CI: 1.025–4.554, p = 0.043) increased the mortality risk after six months of USPD. Conclusion Different risk factors correlated with mortality in older adults with ESRD within and after six months of undergoing USPD, including baseline NYHA class III–IV cardiac function, WBC count, potassium, and calcium levels.